Full Day School Hours On Student Learning Motivation at SMA Negeri 1 Pematangsiantar - Jumaria Sirait; Widya Sridearni Saragih; Eka Seprianti Sihaloho (STABN RADEN WIJAYA WONOGIRI, 2021)
This research aims to analyze the influence of students' perceptions toward the implementation of the full day school system on students' learning motivation at SMA Negeri 1 Pematangsiantar. The study employed a quantitative approach with a causal design through an explanatory survey. The research population included all 11th-grade students in the 2025/2026 academic year, with a sample of 149 students selected using a simple random sampling technique. Data were collected using a Likert scale questionnaire, which had been tested for validity and reliability, and then analyzed using simple linear regression with the aid of SPSS Statistics. The results showed that students' perception of the full day school system has a positive and significant influence on learning motivation, with a coefficient of determination value of 42.7%, a positive regression coefficient of 0.575, and a significance level of p < 0.001. These findings indicate that the more positive students' perception of the full day school implementation, the higher their learning motivation, although the general perception of students remains in the medium to low category due to factors such as fatigue and boredom. This research confirms that the effectiveness of the full day school system heavily depends on students' experience and perception. Therefore, its implementation needs to be managed adaptively and oriented towards student well-being to support sustained learning motivation and academic achievement.